Angular sensor - Saleh, Tanveer; Mohd Razib, Mohd Asyraf; Md. Masud, Rana; Muthalif, Asan G. A. (2016)
This discovery presents methods for angle measurement using CNT forests as a reflector which is first of its kind. The sensor comprised of partially polarized laser source, polarizer, patterned CNT forests and a photo detector to measure the transmitted polarized power coming through a polarizer. CNTs forest was patterned in two different ways, using bottom of the rotating tool and side of the rotating tool. It will generate two different types of surface, trochoidal motion type and anisotropic alignment in the direction of the tool motion. On the first sample, two measurement methods are described here, first by varying the polarization angle, Ɵ1 of the incident laser and second by varying the incident angle itself, Ɵ2. For the second sample, sample is rotated at its axis, Ɵ3 to see the difference in reflectance value.